2015
DOI: 10.3766/jaaa.26.2.4
|View full text |Cite
|
Sign up to set email alerts
|

Effect of a Hybrid Maneuver in Treating Posterior Canal Benign Paroxysmal Positional Vertigo

Abstract: We demonstrated that the GRM as a new treatment is effective in treating PC-BPPV with no benefits to postmaneuver restrictions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 22 publications
0
5
0
Order By: Relevance
“…175,[258][259][260] However, 12.8% to 15.3% of patients will require a second CRP, and 5.1% will be classified as treatment failures after 2 CRPs. 175,[258][259][260] If initial therapy fails, the patient should be reassessed for BPPV diagnosis accuracy. Symptoms of CNS disorders may mimic BPPV, and these conditions would not respond to BPPV treatments.…”
Section: Action Statement Profile For Statement 7amentioning
confidence: 99%
See 2 more Smart Citations
“…175,[258][259][260] However, 12.8% to 15.3% of patients will require a second CRP, and 5.1% will be classified as treatment failures after 2 CRPs. 175,[258][259][260] If initial therapy fails, the patient should be reassessed for BPPV diagnosis accuracy. Symptoms of CNS disorders may mimic BPPV, and these conditions would not respond to BPPV treatments.…”
Section: Action Statement Profile For Statement 7amentioning
confidence: 99%
“…The most effective treatment for BPPV is CRP. Recent studies have shown that the majority of patients are adequately treated with 1 or 2 CRPs (79.4%‐92.7%) 175,258–260 . However, 12.8% to 15.3% of patients will require a second CRP, and 5.1% will be classified as treatment failures after 2 CRPs 175,258–260 …”
Section: Guideline Key Action Statementsmentioning
confidence: 99%
See 1 more Smart Citation
“…Badawy WM et al . [ 20 ] investigated the effect of the GRM with and without post-maneuver instructions and found no difference; they had a very small sample size. This indicates that GRM itself is an effective maneuver therapy, and there is no need for post-maneuver instructions to be given.…”
Section: Discussionmentioning
confidence: 99%
“…According to the practice guideline for BPPV (17), we classified betahistine, labyrinthine sedative, and cinnarizine, which were used in the included studies (27)(28)(29), as AVD in this meta-analysis; VR included the Brandt-Daroff exercise, Cawthorne-Cooksey exercises, and home self-treatment (30); and placebo or no treatment was equivalent to the sham maneuver. The Gans repositioning maneuver (GRM), a hybrid of the Semont and Epley maneuvers, is a relatively new treatment maneuver (31). Due to the lack of a treatment-related recurrence rate in some potential eligible studies, these studies were unable to be included in this network meta-analysis.…”
Section: Characteristics Of the Included Studiesmentioning
confidence: 99%